Multielemental Determination of Rare Earth Elements in Seawater by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) After Matrix Separation and Pre-concentration With Crab Shell Particles - Li, Danyi; Wang, Xunuo; Huang, Ke; Wang, Zenghuan (Frontiers in Environmental Science, 2021)
Considering the unique characteristics of rare earth elements (REEs), the presence of REEs beyond specific limits will adversely affect the environment and it can be employed as a powerful probe for investigating hydrogeochemical processes. This requires sensitive determination of REEs in natural seawater. A matrix separation and pre-concentration technique using the mini-column packed with crab shell particles (CSPs) by inductively coupled plasma mass spectrometry (ICP-MS) as a means of determination has been developed. The aim of the proposed method was to simultaneously determine 16 REEs (Sc, Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu) at trace or ultra-trace concentrations in seawater. The biosorption capacity of CSPs was found to achieve 1.246–1.250 mg g−1 for all elements. In order to optimize performance of the method, the effects of analytical parameters concerning oscillation time, solution pH, salt concentration and eluent concentration were explored. Under the optimal conditions, the detection limits of REEs ranged 0.0006–0.0088 μg L−1, and relative standard deviations (n = 7) varied between 0.55 and 1.39%. The accuracy of developed method was evidenced by applying it to the analysis of REEs in seawater samples, with the overall recoveries at a level of 95.3 and 104.4%. Together, this work provides a promising and cost-effective CSPs-based pretreatment approach for REEs detection in sea environment.